The Effect of Tax Incentives, Account Representatives on Taxpayer Compliance with the Self Assessment System as a Moderation - Novita Sari; Khojanah Hasan; Dwi Anggarani (Optima Science, 2024)
This study was conducted to test whether tax incentives and account representatives have a strong enough influence to increase individual taxpayer compliance during covid19. Meanwhile, this study was also conducted to determine whether tax incentives and account representatives are able to influence individual taxpayers to obey in calculating, depositing, and reporting annual notification letter in a timely manner. This study uses primary data obtained by distributing questionnaires to individual taxpayers in the city of Malang. The data is quantitative which will letter be analyzed using the SPSS 25 application. In this study, it was found that tax incentives and account representatives have a positive and significant effect on individual taxpayer compliance. In this study, it was found that tax incentives had an insignificant effect on taxpayer compliance and account representatives had a significant effect on individual taxpayer compliance. While the self assessmesnt system variable has not been able to moderate tax incentive policies on taxpayer compliance but is able to moderate the performance of account representative on tax payer compliance.